Efektivitas Pembelajaran PAI Berbasis Proyek dalam Meningkatkan Karakter Moderat Mahasiswa: Studi Mixed Methods - Ushwa Dwi Masrurah Arifin Bando; Farhah Utami (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The increasing social polarization and ideological challenges in Indonesia demand the strengthening of the character of religious moderation in universities. This study aims to test the effectiveness of Project-Based Learning (PjBL) in Islamic Religious Education (PAI) courses in improving the moderate character of students and identifying factors that support their success. The research design used mixed methods of sequential explanatory type with 48 students of the Management Study Program, State University of Makassar. Quantitative data were collected through a religious moderation scale instrument validated by a pretest–posttest procedure and analyzed using descriptive statistics and paired sample t-test. Qualitative data were obtained through observation, focus group discussions, and semi-structured interviews, then analyzed thematically. Quantitative results showed a significant increase in the moderate character of students (Pretest M = 70.15; SD = 7.02; Posttest M = 78.64; SD = 6.35; t = 7.82; p < 0.001). Qualitative data reveal that authentic projects, collaborative learning, reflective discussions, and lecturer facilitation play a role in internalizing the values of tolerance, openness, and anti-radicalism. These findings confirm the effectiveness of PjBL as a pedagogical approach to strengthen religious moderation in higher education. The research recommends the integration of PjBL in institutional policies as well as the study of long-term impacts in various educational contexts.